APLIKASI TEKNOLOGI INFORMASI BERBASIS SLiMS DI PERPUSTAKAAN UIN SULTHAN THAHA SAIFUDDIN JAMBI - RUDIANTO, RUDIANTO (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2017)
The rapid development of technology requires every library to improve services continuosly in various aspects. The improvement of Information technology becomes an absolute must tried to achieve the goal of a library. Implementation of automation in library is a process of application done in the library from manual way to digitalization which aims to facilitate librarians in every activity and also facilitate them in tracking information. The implementation of library automation is covered in several areas: cataloging, circulation, OPAC establishment, information alert services, and the procurement of books and magazines. Every services has been automated into one application called SLiMS except the procurement of books and magazines as well as information alert service is still by manual. The causes are constrained to infrastructure, human resources, the systems used are omgood and law of budget. The efforts they undertake, among others, are the submission of letters rectorate request in addition of tools, the asking addition of human resources, and enlarging of the budget.